Industrial Efficiency, Social Order and Moral Purity: Housing Reform Thought in English Canada, 1900–1950 - Purdy, Sean (Urban History Review / Revue d'histoire urbaine, 1997)
Number: 2
Keywords: Logement; Réformistes

Georges-Émile Lapalme: un réformiste engagé, 1930-1960 - Panneton, Jean-Charles (Université du Québec à Montréal, 1999)
Keywords: Lapalme; Georges-Émile; Réformistes

Le mouvement des réformes sociales et la marginalisation des prostituées à Montréal - Lévesque, André (Résistance et transgression. Études en histoire des femmes au Québec, 1995)
Keywords: Femmes; Prostitution; Réformistes

Le mouvement des réformes sociales et la marginalisation des prostituées à Montréal - Lévesque, André (Normes et marginalités. Comportements féminins aux XIXe et XXe siècles. Actes du colloque tenu à l'Université Libre de Bruxelles, les 11-12 mai 1990, 1991)
Keywords: Femmes; Prostitution; Réformistes

Manliness, Goodness, and God: Poverty, Gender, and Social Reform in English-Speaking Montreal, 1890-1929 - Perry, Ann Kirsten (Université Queen's, 1998)
Keywords: Anglophones; Pauvreté; Réformistes

W.D. Lighthall: Sometime Confederation Poet, Sometime Urban Reformer - Wright, Donald A. (Université McGill, 1991)
Keywords: Lighthall; William Douw; Réformistes; Écrivains

Réformisme et catholicisme: la pensée sociale d'Arthur Saint-Pierre - Dupuis, Jean-Claude (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1991)
issued: 1991-24-00
Keywords: Idéologies; Réformistes; École Sociale Populaire

L'enseignement et la pratique de l'hygiène dans les écoles primaires catholiques du Québec de 1905 à 1944: un progrès ou un contrôle? - Duquette, Isabelle (Université de Sherbrooke, 1994)
Keywords: Réformistes

Les mouvements réformiste et constitutionnel à Montréal, 1834-1837 - Muzzo, Johanne (Université du Québec à Montréal, 1990)
Keywords: Rébellions

Les syndicats internationaux et les réformes scolaires au Québec (1900-1930) - Bastien, Céline (Université de Montréal, 1997)
Keywords: Syndicats internationaux

Réforme catholique et altérité: arrière-plan socio-religieux de la fondation de Montréal - Deslandres, Dominique (Les origines de Montréal. Actes du colloque organisé par la Société historique de Montréal, 1993)

Pour une école démocratique: Gérard Filion et les réformes scolaires des années 1960 - Jomphe, Carl (Université du Québec à Montréal, 1998)

La réforme à la ville de Montréal: une expérience de gestion du 3e type? - Laliberté, Marie-France (Université Laval, 1990)

Ward Heelers and Honest Men: Urban Québécois Political Culture and the Montreal Reform of 1909 - Gordon, Alan (Urban History Review / Revue d'histoire urbaine, 1995)
Number: 2
Keywords: Canada (Le); Libéralisme; Patrie (La); Presse (La)

La Fédération des Écoles Normales: Analyse de ses stratégies au moment de la réforme scolaire 1964-1969 - Boisvert, Dominic (Université de Sherbrooke, 1998)
Keywords: Fédération des écoles normales; Écoles normales

Ville et prison: discours d'hygiénistes réformateurs à Montréal au cours de la deuxième moitié du XIXe siècle - Dufresne, Martin (Criminologie, 1995)
Number: 2
Keywords: Médecine; Prisons; Épidémies

Une politique de l'enfance délinquante: la mise en place de l'école de réforme des garçons de Montréal, 1850-1873 - Ménard, Sylvie (Bulletin d'histoire politique, 1998)
issued: 1998-24-00
Keywords: Bourget; Ignace; Délinquance; Enfants; Ultramontains; Évêques

Une bureaucratie en voie de formation: l’administration municipale de Montréal dans la première moitié du XXe siècle - Dagenais, Michèle (Revue d'histoire de l'Amérique française, 1992)
Number: 1
Keywords: Fonctionnaires; Hôtel de ville; Réformistes

Dynamique d'une bureaucratie. L'administration municipale de Montréal et les fonctionnaires, 1900-1945 - Dagenais, Michèle (Université du Québec à Montréal, 1992)
Keywords: Fonctionnaires; Hôtel de ville; Réformistes

Dynamiques d'une bureaucratie: l'administration municipale de Montréal et ses fonctionnaires: 1900-1945 - Dagenais, Michèle (Bulletin du Regroupement des chercheurs-chercheures en histoire des travailleurs et des travailleuses du Québec, 1993)
issued: 1993-22-00
Keywords: Fonctionnaires; Hôtel de ville; Réformistes

Echoing in the Silence of Redemption: Discourses of Nationhood and Identity in Quebec - Gagnon, Michelle (Université Concordia, 1994)
Keywords: Nationalisme; Plante; Pacifique (Plante; Pax); Réformistes; Télévision

"This is our Work": The Women's Division of the Canadian Department of Immigration and Colonization, 1919-1938 - Mancuso, Rebecca (Université McGill, 1999)
Anglophone women, working in a new capacity as federal civil servants, exercised a significant influence on Canadian immigration policy in the interwar years. This dissertation focuses on the women's division of the Canadian Department of Immigration and Colonization, an agency charged with recruiting British women for domestic service from 1919 to 1938. The division was a product of the women's wing of the social reform movement and prevailing theories of gender difference and anglo-superiority. Tracing its nearly twenty years of operations shows how the division, initially regarded as a source of imperial strength and a means of English Canada's cultural survival, came to symbolize the disadvantages of Canada's connection to Great Britain and supposed weaknesses inherent in the female character. This institutional study explores the real and imagined connections among gender, imperialism, and the changing socio-economic landscape of interwar Canada. Lien avec Montréal - dans la thèse
Keywords: Femmes; Fonctionnaires